2001
DOI: 10.4049/jimmunol.167.1.578
|View full text |Cite
|
Sign up to set email alerts
|

A Retro-Inverso Peptide Mimic of CD28 Encompassing the MYPPPY Motif Adopts a Polyproline Type II Helix and Inhibits Encephalitogenic T Cells In Vitro

Abstract: Complete activation of T cells requires two signals: an Ag-specific signal delivered via the TCR by the peptide-MHC complex and a second costimulatory signal largely provided by B7:CD28/CTLA-4 interactions. Previous studies have shown that B7 blockade can either ameliorate experimental autoimmune encephalomyelitis by interfering with CD28 signaling or exacerbate the disease by concomitant blockade of CTLA-4 interaction. Therefore, we developed a functional CD28 mimic to selectively block B7:CD28 interactions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 51 publications
3
34
0
Order By: Relevance
“…Consistent with this structural prediction previously, mutation of Pro 120 has been shown to abrogate the GILZ-p65 interaction (14). Peptides derived from the proline-rich regions of proteins potentially exhibit similar affinity as the entire protein with the interacting partner (7,8,40). We show that the end groups that blocked GILZ-P bind the r-p65 with similar kinetics as the r-GILZ with the strength of interaction in the micromolar range commonly observed for transient intermolecular interactions.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Consistent with this structural prediction previously, mutation of Pro 120 has been shown to abrogate the GILZ-p65 interaction (14). Peptides derived from the proline-rich regions of proteins potentially exhibit similar affinity as the entire protein with the interacting partner (7,8,40). We show that the end groups that blocked GILZ-P bind the r-p65 with similar kinetics as the r-GILZ with the strength of interaction in the micromolar range commonly observed for transient intermolecular interactions.…”
Section: Discussionsupporting
confidence: 61%
“…A conceptually straightforward strategy to develop specific inhibitors of protein-protein interactions is the synthesis of interface peptides derived from the primary sequence of one of the protein binding partners (4). Examples of linear peptides exhibiting PP II conformation include peptides derived from the p85 subunit of PI 3-kinase, CD28-CDR-3 peptide, and protein kinase inhibitors (7)(8)(9).…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…Recently, we identified two biologically active CD28 peptide mimics derived from the CD28 CDR-3-like region. An end group-blocked CD28 peptide (EL-CD28) and its retro-inverso isomer (RI-CD28) were synthesized and characterized for their binding properties and biological activity (23). The synthetic CD28 peptides exhibited similar kinetics of interaction as CD28 for binding the CD80 ligand.…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%
“…The synthetic CD28 peptides exhibited similar kinetics of interaction as CD28 for binding the CD80 ligand. Moreover, the CD28 peptides were observed to interfere with the activation of encephalitogenic T cells in vitro (23).…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%
“…[58][59][60] We have also developed effective inhibitors of vascular endothelial growth factor signaling (VEGF/VEGFR2) 61 that diminish tumor angiogenesis. Furthermore, we have shown that co-targeting HER-2 and VEGF signaling produced superior antitumor effects in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%